Pharmacologic restraint of bovines with gallamine triethiodide - Novaes, Antonio Pereira de; Bügner, Manfred (Pesquisa Agropecuaria Brasileira, 2014)
Gallamine triiodoethylato (GT), a peripheric muscle relaxing was tested as an immobilization drug in bovine. Trials were conducted on 23 bulls weighing from 180 to 410 kilograms, and GT was applied intramuscularly, at 0.49 to 1.86 mg/kilograms of live-weight (KLW). The dose of 1.40 mg/KLW promoted insufficient restraint but doses from 1.50 to 1.60 mg/KLW were efficient in restraining the animals. On the other hand, doses from 1.60 to 1.86 mg/KLW induced respiratory paralysis: however, this side effect could effectively be neutralized by the mixture neostigmine methylsulphate/atropine sulphate. GT alone failed to promote penis protrusion; however, such effect was obtained after washing the preputial cavity with xylocaine 2%, followed by topical massage.